2019
DOI: 10.1186/s13287-019-1269-y
|View full text |Cite
|
Sign up to set email alerts
|

Co-administration of human adipose-derived stem cells and low-level laser to alleviate neuropathic pain after experimental spinal cord injury

Abstract: Background: Evidence has suggested that human adipose-derived stem cells (hADSCs) and low-level laser has neuroprotective effects on spinal cord injury (SCI). Therefore, the combined effect of the hADSCs and laser on neuregeneration and neuropathic pain after SCI was investigated. Methods: Forty-eight adult male Wistar rats with 200-250 g weight were used. Thirty minutes after compression, injury with laser was irritated, and 1 week following SCI, about 1 × 10 6 cells were transplanted into the spinal cord. Mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
33
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 40 publications
(36 citation statements)
references
References 65 publications
1
33
0
Order By: Relevance
“…A recent study reported that intravenous injection of human ASCs inhibited pain-related behavior in a chronic constriction injury (CCI) mouse, STZ-diabetic mouse, and rat model of spinal cord injury for neuropathic pain [ 12 14 ]. Also, other clinical studies reported that intraarticular injection of human adipose-derived stem cells reduced pain responses without serious side effects [ 15 , 16 ].…”
Section: Discussionmentioning
confidence: 99%
“…A recent study reported that intravenous injection of human ASCs inhibited pain-related behavior in a chronic constriction injury (CCI) mouse, STZ-diabetic mouse, and rat model of spinal cord injury for neuropathic pain [ 12 14 ]. Also, other clinical studies reported that intraarticular injection of human adipose-derived stem cells reduced pain responses without serious side effects [ 15 , 16 ].…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, GDNF mRNA expression increased after hADSC transplantation. Stem cells may increase the survival of motor and sensory neurons, improve motor function, induce neurogenesis and axon growth, enhance myelin formation, and relieve pain by regulating GDNF [ 42 ]. Similarly, the use of genetically engineered neural stem cells specifically expressing enhanced green fluorescent protein (for localization) and GDNF in the treatment of spinal cord nerve ligation in spinal nerve ligation (SNL) rats can achieve a more significant effect [ 43 ].…”
Section: The Role Of Stem Cells In the Peripheral Mechanismmentioning
confidence: 99%
“…Additionally, there was a significant reduction in LC3B-II and Beclin1 in the spinal dorsal horn cells, which was related to inflammation and apoptosis [ 67 ]. Experiments by Sarveazad et al and Romero-Ramirez revealed that stem cell therapy increased the number of axons around the cavity and reduced the size of the cavity after spinal cord injury [ 42 , 62 ]. Stem cells reduce spinal cord apoptosis and promote the recovery of injured nerves, which play an important role in the analgesia and treatment of NP.…”
Section: The Role Of Stem Cells In the Spinal Mechanismmentioning
confidence: 99%
“…6,7 Stem cells transplantation has been suggested as a therapeutic option for many conditions. [8][9][10] A systematic review in 2015 showed that administration of mesenchymal stromal cells (MSCs) in animal models of pulmonary fibrosis improved fibrosis, decreased collagen deposition in lung, and reduced the expression of profibrotic chemokines. 11 Although preclinical studies have shown the benefit of MSCs transplantation, this treatment option has some limitations, including the possibility of tumorigenesis.…”
Section: Introductionmentioning
confidence: 99%